Sustainable at both ends: electrochemical CO2 utilization paired with electrochemical treatment of nitrogenous waste. Issue 14 (6th July 2020) - Medvedeva, Xenia V.; Medvedev, Jury J.; Tatarchuk, Stephen W.; Choueiri, Rachelle M.; Klinkova, Anna
Abstract : Optimizing CO2 electrolyzer cell voltage requirement: aqueous and organic reductive electrocatalysis paired with electrooxidation of urea and ammonia. Abstract : We discuss the environmental and energetic benefits of coupling nitrogenous waste treatment with the electrochemical conversion of CO2 to value-added products via direct reduction or electrocarboxylation. In particular, we demonstrate that co-electrolysis of urea or ammonia with CO2 requires significantly lower cell voltages than CO2 electrolyzers relying on the oxygen evolution reaction as an anodic process.